Utilizing 18F‐fluoroethyl‐l‐tyrosine positron emission tomography in high grade glioma for radiation treatment planning in patients with contraindications to MRI. Issue 1 (5th October 2017) - Jaymanne, Dasantha T; Kaushal, Sneha; Chan, David; Schembri, Geoff; Brazier, David; Bailey, Dale; Wheeler, Helen; Back, Michael
Abstract: Introduction: Patients with high grade glioma (HGG) and contraindications to magnetic resonance imaging (MRI) are dependent on contrast‐enhanced computerized tomography (CT) scan imaging for radiation therapy (RT) target volume delineation. This study reviews the experience with the utilization of 18F‐fluoroethyl‐l ‐tyrosine positron emission tomography (FET‐PET) to define residual disease post craniotomy and optimize RT planning. Methods: Patients with HGG and a contraindication to MRI managed with radiation therapy between 2007 and 2015 were identified. RT target volumes including gross tumour volume (GTV) defined by CT‐alone and the biological target volume (BTV) defined by PET‐CT were recorded. Clinical target volumes (CTV) were created from the GTV and BTV respectively using standard protocol volume expansion. The expanded BTV was termed clinical target volume biological (CTV‐B). Union and intersection between CTV and CTV‐B, conformity index, volumetric parameters and individual patient outcomes were analysed. Results: Six patients fit study criteria. There was a mean increase in CTV‐B from CTV by 31.6% with a conformity index of 0.78. Two out of six patients had FET‐PET avid disease outside the constructed PTV when delineated by CT‐alone. One patient with CT‐only planning had a new contrast‐enhancing mass within 1 month of completing RT, suggesting potential geographical miss. Conclusion: Patients with contraindication to MRI the addition of FET‐PET can improve target volume delineation for RT Planning.